Peran Insentif, Perilaku Kepemimpinan, dan Budaya Organisasi terhadap Penguatan Komitmen Organisasi - Jahroni Jahroni; Didit Darmawan; Rahayu Mardikaningsih; Ella Anastasya Sinambela (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
This study intends to find out about the truth that incentives given to employees, effective leadership behavior, and existing organizational culture are thought to have a role in strengthening organizational commitment. The survey is conducted in the production department of a company. Respondents consist of active employees who work at PT. KJA which has 43 employees in the production department. The sampling technique is by census. Regression model, t test, and F test are SPSS-assisted analytical tools. The results showed that incentives, leadership behavior, and organizational culture were proven to have a role in strengthening organizational commitment